Um estudo discursivo das políticas públicas de inclusão na educação do sujeito surdo - (:unkn) unknown (Universidade Federal de Goiás, 2015)
The purpose of this research is to analyze the discourses present in inclusive policies on education of the deaf person, observing the discursive formations that support them. To achieve our goal, we analyze discursive sequences present the following documents: World Declaration on Education for All (1990), Law of Directives and Bases of National Education (LDBEN 9394/96), Salamanca Statement (1994), Law 10,098 / 2000 and 10,436 / 2002, Decree 5626/2005 and the National Policy for Special Education in the Perspective of Inclusive Education 2008 (MEC). Are official documents legislate on inclusive / special education and, inserted this educational proposal, the deaf education . The corpus of our work is composed of sequences discursive selected constants in those mentioned documents. To development of research we have considered in concepts of Discourse Analysis French line, therefore, we rely primarily FD notion of Pêcheux (2009), however, other notions that overlap with the notion of FD were worked such as speech, subject, sense, ideology, interdiscourse and discursive paraphrase. Reflecton questions related to the inclusion of deaf having as reference the research Skliar (2010), Dorziat (1999), (2009), Sardagna (2007), Lopes (2011), Lodi (2013) and others. We also use the cultural identity of notions of Stuart Hall (2006) and constituted identity and marked by the difference as Tadeu Silva (2009). Terms used in deaf education were considered according Dorziat (1999) and analyzed by Possenti (2009b) from the perspective of political correctness movement. Analyses were taken from discursive sequences organized in paraphrastics families groups. Each group of these families was individualized in a specific FD, however, treated with a methodological organization, so during the whole development research, we emphasize the constitutively interdiscourses character of FD found because the interdiscursive relations between the companies make the already-said is constantly resumed, making possible the paraphrastics relations and the explanation of the character intrinsically heterogeneous discourses. The theoretical framework at work in allowed the identification of some speeches, among others, of public policies inclusion for deaf education. They are: the discourse of inclusive school redeeming, economic discourse, the discourse of disability and the cultural discourse. Therefore, found placements, contradictions and dialogues in covenant relationship and opposition in legal texts, and we ascertain, testing, that a speech to constitute relies on other highlighting the continuing relationship maintained between them.
A discursive study of public inclusion in education in the deaf person
Keywords: Formações discursivas; Inclusão; Educação de surdos; Discursive formations; Inclusion; Deaf education; LINGUISTICA, LETRAS E ARTES::LINGUISTICA